Religious Minorities in the Middle East Domination, Self-Empowerment, Accommodation - Nga Longva, Anh; Sofie Roald, Anne (Social, Economic and Political Studies of the Middle East and Asia, 2011)
Focusing on the situation of both Muslim and non-Muslim religious minorities in the Middle East, this volume offers an analysis of various strategies of resilience and accommodation from a historical as well a contemporary perspective. Readership: All those interested in the sociology of religion, majority/minority and ethnic relations, nationalism, state and nation-building, the politics of citizenship, human rights, and the Middle East in general.